‘Alāqoh Hifdzi Nadzmi Tarjamati Al-Jurūmiyyah Bimahāroh Al-Qirōah - Agil, Abdurrahman Ahmad (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2022)
Abstract  Reading is an intellectual activity carried out by a person to gain knowledge or to achieve a purpose, and it is one of the most important windows of human knowledge through which a person views human thought in length, breadth, depth and breadth. Systems of Translation of Al-Ajrumiyya is a book on grammar written by the scholar Sheikh Kayahi Al-Haj Mahmoud Mukhtar Al-Sharbouni. It is considered one of the most important texts of Arabic grammar. Due to the great importance of Al-Ajrumiyya, it has been explained by great scholars and grammarians in the past, and is studied in most linguistic and Sharia universities. Questions in this research: (1) How are students’ efficiency in memorizing the Ajārūmī translation systems and reading skills in the second grade of primary school at Anwar Al-Hasaniyah Institute in Tabalong? (2) How is the relationship between memorizing the Ajārūmī translation systems and the reading skill of the second grade of primary school at Anwar Al-Hasaniyah Institute in Tabalong? In order to obtain the result of the relationship between students’ efficiency in memorizing the Ajārūmī translation systems and reading skill by presenting the students’ results, the researcher used the product moment correlational method. The result appeared according to a correlational analysis that the result of r is 0.687, then we compare it with the result of the table at the 5% level and the sentence N 30, resulting in the result of the table being 0.361. From here we know that the result of r of 0.687 is stronger than the result of the table r of 0.361 at the 5% level, and with this data we know that between conservation Grammar translation systems and reading skill have a positive and tangible relationship, the feasibility of which we have no room to discuss along the lines of this result.                                                                                 Keywords: Ajārūmī translation systems, reading.